Impacts of photovoltaic power generation on very long distribution line - R. Parameechok (2018)
This paper presents impacts of photovoltaic power generation 2 MW on very long distribution line. Therefore, the size of distributed generation has to be carefully considered when it installed on very long distribution system. This study considered following topics: power quality, reliability, stability and voltage profile of very long distribution networks. The simulation results have shown that implementation of the PV grid-connected system could improve power quality and stability, but deteriorate loading level of a distribution feeder.